Transparent photovoltaic memory for neuromorphic device. Issue 10 (2nd March 2021) - Bhatnagar, Priyanka; Nguyen, Thanh Tai; Kim, Sangho; Seo, Ji Heun; Patel, Malkeshkumar; Kim, Joondong
Abstract : Self-powered transparent photovoltaic (TPV) artificial eyes and memory device. Abstract : Bio-inspired electronic devices have significant potential for use in memory devices of the future, including in the context of neuromorphic computing and architecture. This study proposes a transparent heterojunction device for the artificial human visual cortex. Owing to their high transparency, such devices directly react to incoming light to mimic neurological and biological processes in the nervous system. Metal–oxide materials are applied to form a transparent heterojunction (n-type ZnO/p-type NiO) in the proposed device that also provides the photovoltaic function to realize the optic nerve system. The device also exhibits nociceptive features. Its transparent photovoltaic feature endows it with self-powered operation that ensures long-term reliability without needing to replace the power system. This self-powered and highly transparent visual electronic device can provide a route for sustainable applications of neuromorphic computing, including artificial eyes.